Photoacoustic imaging system for fluid flow visualization and biological tissues characterization - Chua, Hui Ling (2020)
Photoacoustic (PA) imaging is a biomedical imaging modality, which work is based on the photoacoustic effect, to provide illumination of biological tissues with strong optical absorption contrast and high spatial resolution at a short scanning time. The drawbacks of some existing PA fluid imaging systems, which include expensive equipment and their maintenance cost, limited sensitivity in detecting signals from restricted regions. This research describes an in-house developed two-axis PA imaging system for investigation of fluid flow and photoacoustic signatures of biological tissues using a continuous laser beam of output wavelength 633 nm to deliver light to the targeted tissue samples and fluid. The resulting acoustic signal detected by a transducer was used to determine the amplitude of tissues optical absorption via the measured phase value (Ф). This research began with the validation of the functionality of the developed system using biological system comprised of a mock circulatory system overlaid by different parts of poultry namely fat, liver and muscle of different sizes. The validated system was then deployed for use on human subjects, and the considered experiment settings included at rest, under warm water and arterial blood flow occlusion conditions. This work reported a consistent increase in the PA signals of all tissues with both sample size and the fluid flow rate. In addition, fat tissues were found to produce the largest PA signals with mean ±standard deviation (SD) Ф = 1.12 ± 0.11, while muscle produced the least signals with Ф = 0.828 ±0.20, which trend agreed well with the previous literature. It was found from the experiments on human subjects that phase difference (ΔФ) was proportional to the change in the velocity of blood flow within microcirculation of an investigated site. The mean and SD of percent relative phase difference for these volunteers were calculated as 51.68 % ± 24.27 % and -68.57 % ± 14.78 % for warm water and blood flow occlusion condition, respectively. The overall sensitivity of the system is 77. 3%. This work concluded the feasibility of this system for non-invasive assessment and visualization of blood perfusion and biological tissues, which deemed it suitable for implementation in healthcare applications.